2016
DOI: 10.1371/journal.pone.0154726
|View full text |Cite
|
Sign up to set email alerts
|

IDH1R132H in Neural Stem Cells: Differentiation Impaired by Increased Apoptosis

Abstract: BackgroundThe high frequency of mutations in the isocitrate dehydrogenase 1 (IDH1) gene in diffuse gliomas indicates its importance in the process of gliomagenesis. These mutations result in loss of the normal function and acquisition of the neomorphic activity converting α-ketoglutarate to 2-hydroxyglutarate. This potential oncometabolite may induce the epigenetic changes, resulting in the deregulated expression of numerous genes, including those related to the differentiation process or cell survivability.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 39 publications
(57 reference statements)
4
24
1
Order By: Relevance
“…Collectively, these experiments suggest that mutant Idh1 likely affects NSCs both directly, as observed through defective differentiation, and indirectly, as observed through a disorganization of the microenvironment, two components with implications in tumor initiation and development (27). This data also corroborates a previous study investigating the role of mutant IDH1 on embryoid body induced human neural stem cells which showed that IDH1-R132H impaired the ability of these cells to differentiate, specifically into the astrocytic and neuronal lineage (28). …”
Section: Resultssupporting
confidence: 91%
“…Collectively, these experiments suggest that mutant Idh1 likely affects NSCs both directly, as observed through defective differentiation, and indirectly, as observed through a disorganization of the microenvironment, two components with implications in tumor initiation and development (27). This data also corroborates a previous study investigating the role of mutant IDH1 on embryoid body induced human neural stem cells which showed that IDH1-R132H impaired the ability of these cells to differentiate, specifically into the astrocytic and neuronal lineage (28). …”
Section: Resultssupporting
confidence: 91%
“…Expression of mutant IDH1 in progenitor cells inhibits differentiation (Figueroa et al, 2010; Lu et al, 2012; Pirozzi et al, 2017; Rosiak et al, 2016; Turcan et al, 2012; Xu et al, 2011). However, the effect of combined IDH mutation and P53/ATRX loss on NSC self-renewal and differentiation is not known.…”
Section: Resultsmentioning
confidence: 99%
“…Our model shows that the combination of the 3 oncogenic hits promotes gliomagenesis not by altering cell growth but by arresting differentiation of NSCs (Pirozzi et al, 2017; Rosiak et al, 2016; Sulkowski et al, 2017), which become locked in a self-renewing and brain-invasive state. Several lines of evidence support the notion that the IDH1 mutation is the inciting oncogenic hit in LGA.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations